Dill seed oil as a possible contraceptive agent: antiangiogenic effects on endothelial cells - Ulus Gönül; Zeytinoğlu Melih; Kürkçüoğlu Mine; Başer Kemal Hüsnü Can; Koparal Ayşe Tansu (Universidade de São Paulo, 2023)
Abstract Dill (Anethum graveolens L.) essential oil is wide spread in the food, beverage and pharmaceutical sectors. Dill is a member of the Apiaceae (Umbelliferae) family. It has the following biological activities: antioxidant, antifungal, antibacterial, antimicrobial, antihyperlipidemic, antihypercholesterolemic, antispasmodic, antiproliferative and anti-inflammatory. Aqueous extract of dill seed has reported effects on sex hormones and infertility potential. Moreover, boiled dill seed has an impact on reducing labor duration in giving birth. Implantation and placentation are necessary for a healthy pregnancy in the early stages. Angiogenesis is responsible for these essential processes. This study aimed to investigate dill seed oil's cytotoxic and antiangiogenic effects on rat adipose tissue endothelial cells (RATECs). Dill seed oil showed dose-dependent cytotoxicity on RATECs. It disrupted endothelial tube formation and depolymerized F-actin stress fibers. According to this study, depolymerization of F-actin stress fiber by dill seed oil could inhibit angiogenesis by suppressing endothelial cell proliferation, tube formation and motility. In other words, dill seed oil can be a new anti-angiogenic agent and a novel contraceptive.